Effect of gas adsorption on electrical resistance of carbon nanotubes - Firouzi, Amin (2010)
Gas sensors have wide applications in everyday life, whether in industry, medical, agriculture and environmental monitoring. A good sensor should be selective, sensitive, responsive, reliable and cost effective. Currently available gas sensors are lacking in one or more of these criteria. Therefore, there is a need to develop new sensing materials and technologies. Since the discovery of Carbon nanotubes (CNTs), their synthesis and application in nanotechnology and Nano-Electro-Mechanical System (NEMS) have been investigated. Many applications have been implemented based on their unique electronic, mechanical, chemical and optoelectronic properties. One area of applications is in gas sensors for detecting oxygen, flammable and toxic gases. In particular, the effect of gas environment on the electronic properties of carbon nanotubes has recently attracted certain attention. Gas adsorption in carbon nanotubes is an important issue for both fundamental research and technical application of nanotubes. This research was carried out to investigate the adsorption effect of carbon dioxide and methane towards the electrical resistance of CNTs thin film. Two different CNTs employed in this research were synthesized by Floating Catalyst Chemical Vapor Deposition (FC-CVD) method on quartz substrate under benzene bubble and methane flow rate as a hydrocarbon source, while ferrocene as a catalyst precursor. Hydrogen and argon act as carrier and purge gas respectively, were fixed for both synthesis. From the research, it can be deduced that FC-CVD method produced high quality CNTs at temperatures of 700˚C and 950˚C for benzene and methane, respectively. The grown CNTs showed good responses to the same concentration of methane and carbon dioxide at room temperature. It was also observed that the CNTs device behaves as a p-type semiconductor when exposed to gaseous molecules. The recovery process is complete only for methane in both samples. Therefore, CNTs should be promising to fabricate novel miniaturized chemical sensors and it is expected that many applications of CNT-based sensors will be explored in future as the interest of the nanotechnology research community.